Yeats Revisited by Kathleen Raine - Montezanti, Miguel Ángel (2015)
It is frequently stated that Yeats is a great poet despite the fact that his mind, tastes and inclinations were dangerously or eccentrically turned to mysterious or mystified matters. It is Kathleen Raine’s contention that, far from being too credulous, Yeats was extremely conscious of his advances in this type of knowledge; and that words such as esoteric, occultism, hermetic lore and some others are more often misunderstood. The Academy misreads Yeats in the same way that it has misread Blake or Shelley. That traditional background is not the one which the Academy usually deals with. Yeats did not write his poems to provide material for doctoral theses but to heal and sustain our human condition. Yeats’s poems related to the Irish Renaissance are concerned with an Ireland of the Imagination. In Kathleen’s opinion, Yeats remains a poet in the traditional sense of the word, not in the modern one. The traditional meaning would account for a speaker of wisdom, truth and the tradition of the Imagination.